EXPLORING SPELLING BEE IN VOCABULARY LEARNING AT AN EQUIVALENCE EDUCATION INSTITUTION : STUDENTS’ VIEWS - Luluk Nur Fadhillah; Mansyur Srisudarso; Mobit Mobit (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This study aimed to explore students’ perceptions and challenges in learning vocabulary through the Spelling Bee method at an equivalency education institution. The research employed a qualitative case study approach involving students from a non-formal education program. Data were collected through interviews and analyzed using thematic analysis. The findings revealed that students generally had positive perceptions toward the implementation of the Spelling Bee method. The activity increased students’ motivation and interest in learning English by creating a fun, interactive, and engaging learning environment. In addition, the method helped students improve their vocabulary mastery, pronunciation, and spelling skills through repeated practice and active participation. Some students also reported that the method supported them in constructing simple sentences, although difficulties in grammar and sentence structure remained. Despite the positive outcomes, several challenges were identified, including anxiety and nervousness during the activity, difficulty in spelling and pronunciation, limited vocabulary knowledge, and challenges in constructing sentences. The findings also highlighted the importance of teacher and peer support in helping students overcome learning difficulties. Overall, the study concludes that the Spelling Bee method is an effective and enjoyable strategy for vocabulary learning in equivalency education, although additional instructional support is still needed to maximize students’ language development.